Influences of Temperature and Length of Storage on the Viability of Gayam (Inocarpus Edible) Seeds - Setyowati, Ninik; Utami, N. W.; Wawo, A. H. (Teknologi Indonesia, 2014)
Research of the influences of temperature and length of storage on the viability of gayam (Inocarpus edible) seeds was carried out at Macropropagation Laboratory, Botany Devision, Research Centre for Biology, Cibinong Science Center. The research was using Randomized Block Design with 3 factors and 3 replications, in which each replication had 5 samples. The first factor was length of storage with 4 levels i.e. 0 (before storage), 1, 2 and 4 weeks. The second factor was temperature of storage with 2 levels i.e. 20C and 26C. The third factor was treatment of seeds with 2 levels of unpeeled (TKPS) and peeled (KPS). The result showed that during the storage, moisture content decreased, value of ion leakage increased and gayam seeds viability decreased. The storage at a temperature of 20C was better than 26C, in which the values of ion leakage were 25599.04 and 34662.85 ?Scm-1, with the seed viability of 83.33 and 80.41%, respectively. Meanwhile the viability of unpeeled seed was better then the peeled one, the viability of unpeeled and peeled seeds were 87.08a, and 76.66b %, respectively. Gayam seeds could be stored up to 4 weeks, at 20C unpeeled seed with a high value of viability (86.66ab %). The research on the water sorption of gayam seeds is necessary to determine the appropriate moisture content of gayam seed storage.